1996
DOI: 10.1074/jbc.271.48.30529
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-like Growth Factor (IGF) Binding Site of Bovine Insulin-like Growth Factor Binding Protein-2 (bIGFBP-2) Probed by Iodination

Abstract: The insulin-like growth factors (IGF-I and IGF-II) 1 are polypeptide mitogens which play diverse roles in development and metabolism across a wide range of vertebrate species (recently reviewed in Ref.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…Removal of either amino-or carboxylterminal residues from IGFBP-1 severely disrupted IGF binding (20,21), whereas deletion of amino acid residues 222-284 of bIGFBP-2 significantly altered the IGF binding capabilities of bIGFBP-2 (22). However, chemical iodination and sitedirected mutagenesis of bIGFBP-2 by Hobba et al (23,24) showed the amino-terminal residue Tyr-60 contributed to IGF binding. NMR analysis and site-directed mutagenesis confirmed the involvement of the equivalent residue of hIGFBP-5 (10,25), whereas recombinant amino-terminal fragments of rIGFBP-3 (26) and hIGFBP-4 (27) have also been shown to retain residual binding affinity.…”
Section: Igfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Removal of either amino-or carboxylterminal residues from IGFBP-1 severely disrupted IGF binding (20,21), whereas deletion of amino acid residues 222-284 of bIGFBP-2 significantly altered the IGF binding capabilities of bIGFBP-2 (22). However, chemical iodination and sitedirected mutagenesis of bIGFBP-2 by Hobba et al (23,24) showed the amino-terminal residue Tyr-60 contributed to IGF binding. NMR analysis and site-directed mutagenesis confirmed the involvement of the equivalent residue of hIGFBP-5 (10,25), whereas recombinant amino-terminal fragments of rIGFBP-3 (26) and hIGFBP-4 (27) have also been shown to retain residual binding affinity.…”
Section: Igfsmentioning
confidence: 99%
“…Briefly, nonspecific interacting proteins were removed with 60 mM imidazole, and specifically bound protein was eluted with 1 M imidazole. Wild-type and truncated bIGFBP-2 preparations were further purified by rpHPLC as described by Hobba et al (23). The eluted protein was detected by absorbance at 215 nm.…”
Section: Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the N-terminus of bovine IGFBP-2, it was shown that Tyr60 was protected against iodination upon binding of IGFBP-2 to IGF-II (Hobba et al 1996). Subsequently, the same group demonstrated that substitution of tyrosine-60 with alanine or phenyalanine leads to a 4.0-and 8.4-fold reduced affinity for IGF-I respectively, and a 3.5-and 4.0-fold reduced affinity for IGF-II respectively (Hobba et al1998).…”
Section: Introductionmentioning
confidence: 99%
“…Initially it was observed that Tyr 60 was protected against iodination upon binding of bovine IGFBP-2 to IGF-II (14), and subsequently, the same group demonstrated that substitution of this amino acid leads to reduced affinities for IGF-I and -II (15). In addition, NMR was carried out on a bacterially expressed N-terminal fragment of IGFBP-5 (residues 40 -92), and this clearly demonstrated that a major IGF-binding domain comprises Val 49 , Tyr 50 (equivalent to Tyr 60 in IGFBP-2), Pro 62 , and Lys 68 -Leu 75 , where the conserved Leu and Val residues localize in a hydrophobic patch on the surface of the IGFBP-5 protein (7).…”
mentioning
confidence: 99%